Continuous higher-order sliding mode control with time-varying gain for a class of uncertain nonlinear systems. (May 2016) - Han, Yaozhen; Liu, Xiangjie
Abstract: This paper presents a continuous higher-order sliding mode (HOSM) control scheme with time-varying gain for a class of uncertain nonlinear systems. The proposed controller is derived from the concept of geometric homogeneity and super-twisting algorithm, and includes two parts, the first part of which achieves smooth finite time stabilization of pure integrator chains. The second part conquers the twice differentiable uncertainty and realizes system robustness by employing super-twisting algorithm. Particularly, time-varying switching control gain is constructed to reduce the switching control action magnitude to the minimum possible value while keeping the property of finite time convergence. Examples concerning the perturbed triple integrator chains and excitation control for single-machine infinite bus power system are simulated respectively to demonstrate the effectiveness and applicability of the proposed approach. Highlights: Continuous higher-order sliding mode control with time-varying gain for a class of uncertain nonlinear systems is achieved. Sliding mode chattering phenomenon is greatly restrained. The minimum admissible value of switching control amplitude is gotten because of the time-varying switching gain and equivalent control method. Transient stability of single-machine infinite bus power system is enhanced.